URGENSI FULL DAY SCHOOL DALAM MENINGKATKAN KOMPETENSI SIKAP SPIRITUAL DAN SOSIAL SISWA DI SMP UNGGULAN NU MOJOAGUNG JOMBANG - Masfufah, Idatul; Anshori, Solihul (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article discusses the urgency of full day school in improving spiritual competence and social students in SMP Unggulan NU Mojoagung Jombang. Using a qualitative approach with interviews, observation, and documentation as a data collection technique, the author uses the Miles and Hubberman models, data reduction, data viewing, and verification / conclusion drawing. The results of the study (1) the competency of the spiritual and social attitudes of SMP Unggulan NU Mojoagung Jombang. School students showed an increase with the implementation of full day school education. Spiritual attitudes related to faith and piety, and morality, independence, democracy, and responsibility to become accustomed. Also a sense of responsibility in fulfilling the obligations of religion. Students carry out worship without being ordered. Students act politely when interacting with the community around their environment, even though everything is inseparable from the support of parents but the habituation done at school is very positive. Keywords: Social and spiritual competence, habituation